Advances in the study of Mexican fisheries with the social-ecological system (SES) perspective and its inclusion in fishery management policy. (1st March 2020) - Peña-Puch, Angelina del Carmen; Pérez-Jiménez, Juan Carlos; Espinoza-Tenorio, Alejandro
Abstract: This study describes the progress of the use of the SES perspective and/or the consideration of users' participation in the scientific literature that study Mexican fisheries, and their inclusion in the fishery management policy. Since 2001, there have been 57 published investigations on 19 fisheries, mostly from the north Pacific (n = 39), focussed mainly on the governance of SES of benthic fisheries, and from the southern Gulf of Mexico and the Caribbean Sea (n = 14), where co-management and the spiny lobster fishery are the most studied. From 21 fisheries having a fishery management plan (FMP), only seven have an international sustainability standard, while another seven fisheries having a sustainability standard have no FMP. In addition, only nine fisheries, with literature that addresses the SES perspective and/or considers the user's participation (out of a total of 19), have a FMP and only four of those fisheries have a sustainability standard. This reflects a mismatch between the interests of the academic, fishery, and government sectors. The SES perspective has been stable in the academic research since 2012, and has been implemented for some fisheries through participatory management processes of international fishery standards; however, this perspective needs to be fully included in Mexican fishery management instruments (e.g., FMPs) and its implementation could be a primary goal for Mexican fishery policy. Graphical abstract: Image 1 Highlights: SES perspective stable in scientific literature on Mexican fisheries since 2012. Mexican north Pacific with most of the SES perspective's literature on fisheries. SES perspective is partially incorporated into the fishery management policy. SES perspective incorporated through participatory process of international standards. Mismatch exists between interests of academic, fishery and government sectors.